Perceived Stress Factors and Coping Mechanisms among Mothers of Children with Sickle Cell Disease in Western Nigeria (1997)
While many studies have looked at the stressful effects of chronic illness of those who suffer such conditions, less is known about the effects on caregivers, especially in developing countries. Mothers in particular must bear the brunt of care and stress for children who have sickle cell disease (SCD). A sample of 200 mothers attending six SCD clinics in both public and private hospitals in the Ibadan-Ibarapa Health Zone of Oyo State, Nigeria, were interviewed. Stress levels were measured using an instrument comprised of stressors listed by mothers themselves in focus group discussions that preceded the survey. Higher levels of stress were associated with less educated and older women, as well as non-married women and those in polygamous households. Stress levels were also greater when there was more than one child with SCD in the family and when the index child was of school age. Coping mechanisms varied according to the category of stressor. Financial stress and disease factors were met with confrontation, while family sources of stress were either complained about, accepted or avoided. Knowledge of the different types of mothers who experience more stress and of their preferred coping mechanisms can be useful in designing clinic-based counselling.